Endoscopic duodenal mucosal resurfacing for the treatment of type 2 diabetes mellitus: one year results from the first international, open-label, prospective, multicentre study. Issue 2 (22nd July 2019) - van Baar, Annieke C G; Holleman, Frits; Crenier, Laurent; Haidry, Rehan; Magee, Cormac; Hopkins, David; Rodriguez Grunert, Leonardo; Galvao Neto, Manoel; Vignolo, Paulina; Hayee, Bu'Hussain; Mertens, Ann; Bisschops, Raf; et al.
Abstract : Background: The duodenum has become a metabolic treatment target through bariatric surgery learnings and the specific observation that bypassing, excluding or altering duodenal nutrient exposure elicits favourable metabolic changes. Duodenal mucosal resurfacing (DMR) is a novel endoscopic procedure that has been shown to improve glycaemic control in people with type 2 diabetes mellitus (T2D) irrespective of body mass index (BMI) changes. DMR involves catheter-based circumferential mucosal lifting followed by hydrothermal ablation of duodenal mucosa. This multicentre study evaluates safety and feasibility of DMR and its effect on glycaemia at 24 weeks and 12 months. Methods: International multicentre, open-label study. Patients (BMI 24–40) with T2D (HbA1c 59–86 mmol/mol (7.5%–10.0%)) on stable oral glucose-lowering medication underwent DMR. Glucose-lowering medication was kept stable for at least 24 weeks post DMR. During follow-up, HbA1c, fasting plasma glucose (FPG), weight, hepatic transaminases, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), adverse events (AEs) and treatment satisfaction were determined and analysed using repeated measures analysis of variance with Bonferroni correction. Results: Forty-six patients were included of whom 37 (80%) underwent complete DMR and 36 were finally analysed; in remaining patients, mainly technical issues were observed. Twenty-four patients had at least one AE (52%) related to DMR. Of these, 81% were mild. One SAE and no unanticipated AEs were reported. Twenty-four weeks post DMR (n=36), HbA1c (−10±2 mmol/mol (−0.9%±0.2%), p<0.001), FPG (−1.7±0.5 mmol/L, p<0.001) and HOMA-IR improved (−2.9±1.1, p<0.001), weight was modestly reduced (−2.5±0.6 kg, p<0.001) and hepatic transaminase levels decreased. Effects were sustained at 12 months. Change in HbA1c did not correlate with modest weight loss. Diabetes treatment satisfaction scores improved significantly. Conclusions: In this multicentre study, DMR was found to be a feasible and safe endoscopic procedure that elicited durable glycaemic improvement in suboptimally controlled T2D patients using oral glucose-lowering medication irrespective of weight loss. Effects on the liver are examined further. Trial registration number: NCT02413567